2011
DOI: 10.5005/johcd-5-1-42
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Mucosal Changes in Eluru, Andhra Pradesh (India) - An Institutional Study

Abstract: Objective: The objective of the study was to evaluate the prevalence of oral mucosal changes (OML) in Eluru, Andhra Pradesh and to determine possible associations of OML with respect to age, gender and habits. Materials and Methods: The study sample consisted of 3035 patients collected from outpatients seeking dental treatment in department of Oral Medicine and radiology. The subjects were interviewed by trained interviewers and underwent a clinical examination of the oral mucosa performed according to WHO gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…[33] in Eluru, Andhra Pradesh, India, which found a total of 1489 lesions in which 929 mucosal changes were either normal mucosal variants or developmental anomalies. In another study by Jahanbani et al .,[34] oral developmental lesions were seen in 295 patients (49.3%), Fordyce granules only (27.9%), fissured tongue (12.9%), leukoedema (12.5%), and hairy tongue (8.9%).…”
Section: Discussionmentioning
confidence: 99%
“…[33] in Eluru, Andhra Pradesh, India, which found a total of 1489 lesions in which 929 mucosal changes were either normal mucosal variants or developmental anomalies. In another study by Jahanbani et al .,[34] oral developmental lesions were seen in 295 patients (49.3%), Fordyce granules only (27.9%), fissured tongue (12.9%), leukoedema (12.5%), and hairy tongue (8.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence in India varies from 0.4% to 9.5%. [14] Results obtained from other studies showed prevalence rates of 1.18%, [2] 0.89%, [3] and 4.4%. [17] These lesions are more prevalent in men due to increased usage of tobacco smoke among them.…”
Section: Tobacco Induced Non-neoplastic Oral Mucosal Lesionsmentioning
confidence: 97%
“…[15] Indian studies have shown prevalence rates of 0.25%, [3] 0.84%, [17] and 0.13%. [2] Refraining from habit or repeated washing clears the stain and discontinuance of the betel quid chewing habits leads to nearly complete clearance of the encrustation. [14] Leukedema is a chronic white mucosal condition in which the oral mucosa has a grey opaque appearance.…”
Section: Tobacco Induced Non-neoplastic Oral Mucosal Lesionsmentioning
confidence: 99%
See 2 more Smart Citations